Handbook of Research on Transitional Justice and Peace Building in Turbulent Regions (2016)
In the era of globalization, awareness surrounding issues of violence and human rights violations has reached an all-time high. In a world where billions of human beings have the potential to create endless destruction, these same individuals are capable of working cooperatively to create adequate solutions to current global problems.